Elective pelvic nodal irradiation with a simultaneous hypofractionated integrated prostate boost for localized high risk prostate cancer: Long term results from a prospective clinical trial. (October 2021) - Glicksman, Rachel M.; Loblaw, Andrew; Morton, Gerard; Szumacher, Ewa; Chung, Hans T.; Vesprini, Danny; Chu, William; Liu, Stanley K.; Choo, Richard; Deabreu, Andrea; Mamedov, Alexandre; Zhang, Liying; et al.
Highlights: Long-term results of elective nodal irradiation and hypofractionated prostate boost. At 10 years, biochemical failure 33%, distant metastasis 17% and survival 76% Low cumulative incidence of grade ≥3 gastrointestinal and genitourinary toxicity. Abstract: Background: To report on long-term results of elective pelvic nodal irradiation (EPNI) and a simultaneous hypofractionated prostate boost for high-risk prostate cancer. Materials and methods: This was a prospective single-arm study. Patients with high-risk disease (cT3, PSA >20 ng/mL, or Gleason score 8–10) were eligible. Patients received 45 Gy in 25 fractions to the prostate and pelvic lymph nodes with a simultaneous intensity-modulated radiotherapy boost of 22.5 Gy to the prostate (total dose 67.5 Gy in 25 fractions), with androgen deprivation therapy (ADT) for 2–3 years. The primary endpoint was biochemical failure. Secondary endpoints included distant metastases and overall survival. Multivariable analysis was performed to look for predictive factors. Late toxicity was assessed using CTCAE v3.0. Results: 230 patients enrolled. Median follow-up was 11.2 years (IQR 8.1–12.9). At 10 years, cumulative incidence of biochemical failure was 33.4%, distant metastasis was 16.5%, and overall survival was 76.3%. On multivariable analysis, PSA nadir ≥0.05 ng/mL was associated with biochemical failure (HR 6.8, 95% CI 4–11.8, p < 0.001) and distant metastases (HR 7.5, 95% CI 3.9–14.5, p < 0.0001). PSA nadir ≥0.1 ng/mL (HR 5.2, 95% 2.2–12, p = 0.0001) and ADT use ≤12 months (versus >24 months) (HR 2.3, 95% CI 1.3–3.9, p = 0.004) were associated with worse survival. The 5-year cumulative incidence of any late grade ≥3 gastrointestinal and genitourinary toxicity was 2.3% and 7.5%, respectively. Conclusion: EPNI and a simultaneous hypofractionated prostate boost combined with long-term ADT for high-risk prostate cancer resulted in acceptable 10-year biochemical control and survival with low grade ≥3 toxicity.